A FLOOD OF 2010 IN UNIÃO DOS PALMARES -AL: SOCIAL AND ENVIRONMENTAL IMPACTS IN COASTAL AREAS - Silva, Maria Aparecida da; Moreira, Manoel Simeão (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
The aim of this paper was to analyze the impacts that social and environmental impacts caused to areas border the Rio Mundaú in Uniao dos Palmares-AL after the flood of 2010. The areas most affected were the ones that are on the river and its tributary creek Mundaú Cana Brava, which its population had significant amount riverside people. The methodology we used was the literature and observation of the affected areas, through visits in locus before, during and after the flood. What happened was a great flood that devastated these riparian areas, leaving many people homeless and displaced, destroying the structural and dreams of people. Besides the change in the social life of the people and the environment, there were also significant changes in the landscape of the riverside areas of Rio Mundaú. The river banks have been changed completely, which was once occupied by houses and a heavy flow of residents currently see only debris, scrub and isolated areas, completely abandoned by their former inhabitants and the government. By being abandoned for the risk of invasions of homeless people or even old residents, who have no prospect of achieving better houses. The flood was a watershed in the recent history of Uniao dos Palmares, when it comes to infrastructure and development of new neighborhoods, because even with the creation of precarious housing and structural development of a breakthrough, it provided an economic development for the city and some improvements for the population.